Computer Program for the Analysis of Loads on Buildings Using the ASCE 7-93 Standard Minimum Design Loads on Buildings and Other Structures - Browning, Stephen E. (Virginia Tech, 2014)
A computer program for the analysis of loads on buildings is developed. The program determines wind loads, earthquake loads, and snow loads according to the ASCE 7-93 Standard Minimum Design Loads for Buildings and Other Structures (ASCE 7-93). The program is developed using the object-oriented programming methodology and runs on the Microsoft Windows 95 graphical environment. It is a valuable and useful tool for determining loads on buildings. === Master of Engineering